Body-Art, poging tot een voorlopige benadering. ([S.l.] : [s.d.])
Abramovic, Marina & Ulay ; Acconci, Vito ; Ben ; Burden, Chris ; Chiraga, Casuo ; Duchamp, Marcel ; Export, Valie ; Gilbert & George ; Gutai Group ; Kaprow, Allan ; Klein, Yves ; Lüthi, Urs ; Manzoni, Piero ; Marannes, Philippe ; Mathieu, Georges ; Messager, Annette ; Mol, Pieter Laurens ; Murakami, Saburo ; Nauman, Bruce ; Nitsch, Hermann ; Ontani, Luigi ; Oppenheim, Dennis ; Pollock, Jackson ; Rainer, Arnulf ; Rinke, Klaus ; Samaras, Lucas ; Schiele, Egon ; Schwarzkogler, Rudolf ; Schwitters, Kurt ; Sélavy, Rrose ; Le Va, Barry ; Weibel, Peter ; Yoshikara, Mishio
eindwerk